SECURE-AND-PRESERVE RESEARCH OF THE OKTYABRSKIY I AND KIEVSKIY I BURIAL GROUNDS OF EARLY ALANIAN CULTURE AT THE MIDDLE TEREK IN MOZDOK DISTRICT OF THE REPUBLIC OF NORTH OSSETIA-ALANIA IN 2019 - Malasev, Vladimir Ur'evic; Magomedov, Rabadan Gadzievic; Dzucev, Feliks Safarbekovic; Mamaev, Hamid Magomedovic; Kadzaeva, Zalina Petrovna (History, Archeology and Ethnography of the Caucasus, 2020)
In May-August of 2019, Terek comprehensive archeological expedition (LLC “Research and production center «DARS»”), Caucasian expedition (Institute of archeology of RAS) and Chechen expedition (Institute of humanitarian studies of AS of Chechen Republic), with the financial support of PJSC “Gazprom” (LLC “Gazprom Invest”, Saint-Petersburg) and LLC “Kirus” (Grozny), conducted secure-and-preserve digs of burial grounds Oktyabrskiy I and Kievskiy I of the early Alanian culture on the construction site of the main gas pipeline “Mozdok-Grozny” in Mozdok district of the Republic of North Ossetia-Alania. At Oktyabrskiy I burial ground, the following burials were studied: 122 mound and non-mound burial complexes of the 3rd – first half of the 5th century AD, on Kievskiy I – 40 complexes of the second half of 4th – first half of the 5th century AD, and one burial of the 14th century AD. The vast majority of the burials were made in catacombs of the Type I (the long axis of the chamber is perpendicular to the long axis of the entrance pit). The studied sample of burials supplements the results of excavations of 2018 and makes the studied monuments supporting for the territory of the Middle Terek at the time indicated. The population, which abandoned the burials of the type Bratskiy I mounds, Oktyabrskiy I and Kievskiy I, participated in cultural and historical processes in the territory of the West Peri-Caspian region, where their presence in the second half of the 3rd century AD has been recorded in the Tersko-Sulak interfluve since the middle of the 4th century AD – in southern Dagestan, as well as on the northern outskirts of the Kislovodsk basin.
Keywords: Republic of North Ossetia-Alania; security and rescue excavations; Kievsky-I and Oktyabrsky-I burial ground mounds; Alan culture; 3rd – first half of the 5th century AD.